Role of cord blood IGF-1 and maternal HbA1c levels to predict interventricular septal hypertrophy among infants of diabetic mothers: A case-control study. (April 2023) - Chandra, Tharuna; Tripathi, Shalini; Tiwari, Ashish; Sonkar, Gyanendra; Agarwal, Smriti; Kumar, Mala; Singh, S.N.
Abstract: Background: Infants of diabetic mothers (IDMs) develop interventricular septal hypertrophy (ISH) (> 6 mm) [1] . The proportion of IDMs developing ISH varies from country to country. Maternal HbA1c and cord blood Insulin-like growth factor-1 (IGF-1) levels have been found useful to predict ISH. Methods: This was a case-control study of term neonates of diabetic mothers (cases) and of non-diabetic mothers (controls) to evaluate echocardiographic (ECHO) differences among cases and controls and to find the correlation of interventricular septal thickness (IVS) thickness with maternal HbA1C and cord blood IGF-1 levels. Results: Of 32 cases and 34 controls (mean gestational age 37.7 ± 0.9 weeks), 15 (46.8 %) cases, no control developed ISH. Septal thickness was more (6 ± 0.15 cm vs 3 ± 0.06 cm; p  = 0.027) in cases than controls. Functional ECHO parameters including left ventricle ejection fraction were comparable ( p  = 0.9) among the two groups. Maternal HbA1C levels were higher (6.5 % ± 1.3 vs 3.6 % ± 0.7; p  = 0.001) with a positive correlation with IVS (Pearson's coefficient 0.784, p  < 0.001). Cord blood IGF1 levels were too higher in cases (99.1 ± 6.09 ng/ml vs 37.1 ± 2.99 ng/ml; p < 0.001) with moderate correlation with IVS thickness (Pearson's coefficient 0.402; p = 0.00). Receiver operator curve analysis showed, that at a cut-off of 72 ng/ml, cord blood IGF1 predicted ISH with 72 % sensitivity; 88 % specificity and at a cut-off of 7.35 %, maternal HbA1c predicted ISH with sensitivity; specificity of 93.8 % and 72.1 % respectively. Conclusion: ISH was present in 46.8 % in cases as compared to none in controls. IVS thickness correlated well with maternal HbA1C and moderately with cord blood IGF-1 levels. Functional parameters on ECHO were unaffected by maternal diabetic control. At the cut-off of maternal HbA1c of 7.35 % and cord blood IGF-1 of 72 ng /ml, babies need to be monitored clinically with ECHO to look for ISH. Highlights: Interventricular septal hypertrophy (ISH) was present in 46.8 % of Infants of diabetic mothers as compared to none in controls. Septal thickness correlated well with maternal HbA1C and moderately with cord blood Insulin like growth factor-1 (IGF-1). At maternal HbA1c of 7.35% and cord blood IGF-1 of 72 ng /ml, babies need to be monitored clinically and by echocardiogram to look for ISH.